1986
DOI: 10.1073/pnas.83.15.5392
|View full text |Cite
|
Sign up to set email alerts
|

Expression and site-specific mutagenesis of the poliovirus 3C protease in Escherichia coli.

Abstract: We have engineered a segment of the poliovirus genome (nucleotides 5438-6061) that encodes the 183 amino acid residues of the 3C region and 25 residues of the 3D region of the viral polyprotein into an Escherichia coli expression vector. The 3C region is a virus-specific protease, which, when expressed in E. coli, is shown to be active and autocatalytic. In our system, three poliovirus-specific proteins are produced: a precursor polyprotein (3C-3D), an internal initiation product, and the mature protease (3C).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 27 publications
5
73
0
Order By: Relevance
“…This protease has been characterized as a cysteine protease (Argos et al, 1984) and by sequence comparison of several different picornaviruses two conserved amino acids have been implicated as reactive residues in the active site (Werner et al, 1986). Furthermore these amino acids have been shown to be directly involved in the active site of 3C from PV (Ivanoff et al, 1986). Sequence analysis of the 3C-3D junction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This protease has been characterized as a cysteine protease (Argos et al, 1984) and by sequence comparison of several different picornaviruses two conserved amino acids have been implicated as reactive residues in the active site (Werner et al, 1986). Furthermore these amino acids have been shown to be directly involved in the active site of 3C from PV (Ivanoff et al, 1986). Sequence analysis of the 3C-3D junction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[5]). The functional importance of these two residues has been subsequently confirmed by sitedirected mutagenesis [9], though direct test of the hypothesis has not been reported. Due to the different location of the (putative) catalytic Cys residues and to the lack of overall sequence similarity, it was suggested that 3C-like proteases were not evolutionarily related to other cysteine proteases [5], their formal analogy being explained by convergence.…”
Section: Introductionmentioning
confidence: 95%
“…Despite the similarity in the positioning of the (putative) catalytic residues in 3C p~° and chymotrypsin-like enzymes, Cys and Ser are not as easily interchangeable in the triad as could be imagined. Thus Cys 147 to Ser substitution in poliovirus 3C Pr° completely abolished its protease activity [9]. In nature, however, such substitutions appear to work as exemplified by the putative protease of SBMV; presumably this is gratified by some compensatory substitution(s).…”
Section: A Chymotrypsin-like Structural Fold In 3c Pr°mentioning
confidence: 99%
See 1 more Smart Citation
“…The 3C and 3C-related proteases also contain a substratebinding pocket which determines the cleavage site specificity (Bazan & Fletterick, 1988 ;Dougherty et al, 1989 ;Gorbalenya et al, 1989 ;Nienaber et al, 1993 ;Allaire et al, 1994 ;Matthews et al, 1994). In particular, a histidine residue located in the Cterminal region of the protease is directly involved in the recognition of a glutamine (or glutamate) residue at the k1 position of the cleavage sites of picorna-, poty-and comovirus polyproteins (Bazan & Fletterick, 1988 ;Gorbalenya et al, 1989 ;Allaire et al, 1994 ;Matthews et al, 1994 ;Ivanoff et al, 1986 ;Dougherty et al, 1989 ;. The proteases of nepoviruses of subgroups a and b do not contain a histidine residue in their substrate-binding pockets and recognize cleavage sites that differ from the (Q, E)\(G, S, M) consensus of the aforesaid polyproteins (see Mayo & Robinson, 1996 ;Sanfaçon, 1995 and references therein).…”
Section: Introductionmentioning
confidence: 99%